Visual Interactive Virtual Object: Development of Whisk AI Based Animated Video Media to Improve Science Learning Outcomes - Prananda, Gingga; Tubo, Mariane Bitacura; Supriatna, Eka; Judijanto, Loso (Universitas Muhammadiyah Mataram, 2026)
The rapid development of digital technology in education requires innovative learning media that can help elementary students understand abstract science concepts more effectively. However, many elementary science learning practices still rely on conventional explanations that limit students’ conceptual visualization and interactive engagement. This gap indicates the need for technology-integrated media that combine visual representation and interactive learning experiences. Therefore, this study aimed to develop and examine the validity, practicality, and effectiveness of WHISK AI–based animated video learning media integrating the VIVO (Visual Interactive Virtual Object) concept in elementary science learning. The novelty of this research lies in the integration of artificial intelligence assisted animated video development with interactive virtual object visualization (VIVO), which has not been widely implemented in elementary science learning to support the visualization of abstract concepts through visual interactive scaffolding. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were fifth-grade students from SDN 06 KL and SDN 13 LB in West Sumatra during the second semester of the academic year. Data were collected through expert validation sheets, teacher practicality questionnaires, student response questionnaires, observations, and learning outcome tests using a one-group pretest–posttest design. Data analysis techniques included descriptive quantitative analysis using mean scores to determine validity and practicality levels, as well as normalized gain (N-gain) analysis to measure learning effectiveness. The validation results from six experts (language, content, and educational technology experts) showed an average score of 4.32, categorized as highly valid. The practicality test involving six teachers produced an average score of 4.40, indicating that the media are highly practical. Furthermore, the effectiveness test conducted with 80 students demonstrated a moderate improvement in learning outcomes, with an average N-gain score of 0.57, indicating meaningful conceptual improvement after the implementation of the developed media. Based on these findings, the WHISK AI–based animated video learning media integrating the VIVO concept are valid, practical, and effective in improving students’ understanding of abstract science concepts. Pedagogically, the integration of AI-generated animation and interactive virtual visualization provides structured visual scaffolding that supports conceptual construction, increases student engagement, and strengthens technology-integrated science learning at the elementary level. Therefore, this media can serve as an innovative alternative to enhance digital-based instructional practices in elementary science education.